Ethnoscience: A Philosophical Study with Anthropological, Ontological and Axiological Perspectives - Amiruddin, Mohd Zaidi Bin; Nahadi, Nahadi; Anwar, Sjaeful; Samsudin, Achmad; Suhandi, Andi; Aminudin, Adam Hadiana (FKIP ULM, 2024)
One of the emerging scientific developments is science-based local wisdom, or